2019
DOI: 10.29356/jmcs.v63i1.564
|View full text |Cite
|
Sign up to set email alerts
|

Propiconazole nanoencapsulation in biodegradable polymers to obtain pesticide controlled delivery systems.

Abstract: The nanoencapsulation of pesticides in biodegradable polymers confers several advantages to conventional agrochemicals, such as protection against losses due volatilization and degradation of the active ingredient, as well as the augment of water dispersion, allowing for their application on crops without requiring the use of organic solvents that could harm the user and the environment. This characteristics could enhance the productivity, reducing both costs and environmental pollution. In this work the propi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Sousa et al 47 obtained such an inhibitory effect in root and shoot growth of two weeds species when using 10 times less atrazine in a nanoencapsulated form compared to a standard formulation. Barrera-Meńdez et al 48 obtained twice longer antifungal activity by the use of an encapsulated propiconazole formulation than a commercial one.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Sousa et al 47 obtained such an inhibitory effect in root and shoot growth of two weeds species when using 10 times less atrazine in a nanoencapsulated form compared to a standard formulation. Barrera-Meńdez et al 48 obtained twice longer antifungal activity by the use of an encapsulated propiconazole formulation than a commercial one.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The adsorption of the pesticide or herbicide on the nanoparticle surface requires derivatization of nanoparticles (when a covalent adhesion is desired), or it simply occurs by incubating the active molecule with the nanoparticle suspension (when a reversible adhesion is desired). In 2019, Barrera-Méndez et al encapsulated propiconazole fungicide in PLA nanospheres and evaluated their efficiency in treating the Fusarium dieback disease [ 58 ]. Based on the release profile and antifungal activity, the nanospheres presented an improved performance than the commercial form of propiconazole, revealing a sustained release during 55 h.…”
Section: Structure Of Polymer-based Nanopesticidesmentioning
confidence: 99%
“…Sun et al [141] stated that the nano-abamectin formula based on polylactic acid contributes to its solubility and leads to higher insecticidal activity against the pea aphid (Acyrthosiphon pisum). Furthermore, Barrera-Méndez et al [142] expressed that polymeric nanocarrier-based encapsulated pesticides exert an effective role in the release and good dispersion of these agrochemicals. They revealed that encapsulation of propiconazole using polymer polylactic acid and co-polymer poly (lacticco-glycolic) acid increases the inhibitory effect of propiconazole against Fusarium solani due to the more effective release of propiconazole compared to its commercial formulation.…”
Section: Polymeric Nanocarriersmentioning
confidence: 99%